Mild synthesis of environment-friendly thermoplastic triblock copolymer elastomers through combination of ring-opening and RAFT polymerization. Issue 26 (31st May 2019) - Fang, Chu; Wang, Xuehui; Chen, Xuesi; Wang, Zhigang
Abstract : Environment-friendly thermoplastic triblock copolymer elastomers, polylactide- block -polyisoprene- block -polylactide, were synthesized by a mild ROP and RAFT method. Abstract : Structurally well-defined environment-friendly thermoplastic triblock copolymer elastomers, polylactide- block -polyisoprene- block -polylactide (PLA- b -PI- b -PLA), were synthesized by a creative mild method, which combines ring-opening polymerization (ROP) and subsequent reversible addition-fragmentation chain transfer (RAFT) polymerization. A PLA-based macromolecular chain transfer agent (PLA-CTA) was first synthesized by ROP from the monomerl -lactide (LA) initiated by a specifically prepared di-hydroxyl-terminated chain transfer agent 1, 4-phenylenebis(methylene)bis(2-hydroxyethyl) dicarbonotrithioate (PMHD) with 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) serving as a nonmetallic catalyst. Then, a series of PLA- b -PI- b -PLA triblock copolymers were synthesized via RAFT polymerization by using the PLA-CTA and isoprene with di- tert -butyl peroxide (DTBP) as the initiator. In these triblock copolymers, PLA end blocks were dispersed as hard microdomains in the rubbery PI matrix as revealed by two distinct glass transition temperatures from differential scanning calorimetry and by typical phase-separated morphologies from transmission electron microscopy observation. By tuning the molecular mass of the PI midblock, these triblock copolymers could show behavior ranging from thermoplastics to thermoplastic elastomers, with the highest tensile strength of 13 MPa or elongation at break of 1424%. Furthermore, mechanical properties of these triblock copolymers could be easily manipulated by adjusting the molecular mass of the PI midblock. This efficient, facile and mild synthesis method in this work can be further applied to develop more environment-friendly elastomers with desired mechanical properties.